Biograph Orchestra - Delluc, Louis (Iluminace, 1993)
An essay on music in cinema by a key author and theorist of the French film avant-garde of the 1920s. Translated by Tereza Limanova.
Keywords: music in cinema; French film avant-garde; Louis Delluc